Considerable qualitative variability in local-level biodiversity surveys in Finland: A challenge for biodiversity offsetting - Kalliolevo Hanna; Salo Matti; Hiedanpää Juha; Jounela Pekka; Saario Tapio; Vuorisalo Timo (Elsevier GmbH, 2022)
High-quality biodiversity monitoring is crucial in the era of rapid global biodiversity loss and for the evaluation of conservation outcomes at different spatial scales. Biodiversity offsets are conservation actions that aim to an outcome of no net loss of biodiversity by compensating for the negative impacts from development projects. Successful use of offsets requires that the biodiversity gains and losses between offset and development areas are adequately and comparably measured. Numerous local-level biodiversity surveys are conducted to estimate the biodiversity values of potential development areas in Finland every year. These surveys are done for local planning purposes, and their results are almost never published. We studied Finnish biodiversity surveys to assess their adequacy with regards to biodiversity offsetting. Our data included all biodiversity surveys (n = 206) documented in the region of Southwest Finland during the time period of 1997–2014. We analysed the surveys based on Finnish nature legislation and biodiversity related criteria gathered from other offset and conservation programs. We found the surveys to be inadequate in their assessment of nature values and spatial considerations for offset purposes. We used cluster analysis to study the differences between surveys based on the inventoried nature values and found surveys were clustered into 3 different groups. The characteristics of surveys also varied between individual surveyors. Our results show that the current execution of biodiversity surveys is not compatible enough with the quality of surveys needed for biodiversity offsets. Surveys must be standardized to ensure their comparability and sufficient measurement of biodiversity with ecologically and geographically important features.